The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1136/vr.d2360
|View full text |Cite
|
Sign up to set email alerts
|

Selected haematological and plasma chemistry parameters in juvenile and adult degus (Octodon degus)

Abstract: Thirty-five juvenile (mean age 6.3 weeks) and 35 adult (mean age 2.0 years) healthy degus (Octodon degus) were studied to investigate selected haematological and plasma biochemistry parameters. Animals were anaesthetised with isoflurane, and blood was withdrawn from the cranial vena cava. Erythrocyte, haematocrit and neutrophil counts (including the percentage of neutrophils) were significantly higher in the adult degus than in the juveniles. In contrast, the reticulocyte count, mean corpuscular volume, mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…29,30,51 The same age-related effect on BUN has been described in older degus, and the difference was suggested to be due to higher protein metabolism in younger animals. 27 Similar to older prairie dogs, older guinea pigs tend to show Arrows indicate the trend with increasing age. a Value differed significantly (P < 0.05) between juvenile and adult animals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…29,30,51 The same age-related effect on BUN has been described in older degus, and the difference was suggested to be due to higher protein metabolism in younger animals. 27 Similar to older prairie dogs, older guinea pigs tend to show Arrows indicate the trend with increasing age. a Value differed significantly (P < 0.05) between juvenile and adult animals.…”
Section: Discussionmentioning
confidence: 97%
“…50,51 However, our older prairie dogs tended to show a decrease in albumin concentration and increases in the total protein and globulin concentrations compared with juvenile animals, and similar trends have been reported for guinea pigs, rats, and degus (Octodon degus). 27,29,46 Older mice and rats tend to show lower blood glucose concentrations. 14,29 In our current study, older prairie dogs had significantly lower blood glucose than juvenile animals, and this was also previously described in wild-caught prairie dogs tested using the same veterinary POC analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the PCV, Hbc and RBC count of the juvenile African giant rats showed narrow range of values which are typical of many rodents such as the birch mouse (Wolk 1985), inbred juvenile cotton rat (Robel et al 1996), adult African giant rat (Oyewale et al 1998b), laboratory albino rat (Ihedioha et al 2004), African soft-furred rat (Kagira et al 2005), wild African grasscutter (Opara et al 2006) and brush-tailed rat (Jekl et al 2011). The mean RBC count recorded in this study is higher than that reported for wild juvenile cotton rat (Robel et al 1996) and juvenile laboratory rat (Ihedioha et al 2004), and not different from that reported for the mole rat (Broekmann et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The significant differences in the serum ALT activity and serum albumin concentration in the female and male juvenile African giant rat were not clearly understood and neither is its significance, but may be attributed to the differences in their metabolic activities (Onwuka et al 2003). The significantly higher serum BUN level in females than males without a significant concurrent increase in serum creatinine level suggests a high protein metabolism in females than males (Jekl et al 2011). The differences in the values of the serum biochemistry parameters in the present study and those reported by Nssien et al (2002) and Onwuka et al (2003) (south-western Nigeria) may be attributed to climatic factors such as temperature and humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Females have four pairs of mammary glands, and the testicles of males are intra-abdominal (Bates and Weir, 1944;Contreras and Bustos-Obregon, 1980;Weir, 1970). Reference values for selected hematologic and serum chemistry values for degus have been published and are similar to values reported for guinea pigs and rats (Murphy et al, 1978;Jekl et al, 2011c). The degu spleen is unusual, with sinusoids lined by endothelial cells having cuboidal morphology that gives the spleen a glandular appearance (Murphy et al, 1980).…”
Section: B Biologymentioning
confidence: 88%